Memahami Permasalahan Golongan Terpinggir di Bandar:Kajian Kes Gelandangan di George Town, Pulau Pinang: Understanding the Problems of Marginalized Group in City:A Case Study of Homeless People in George Town, Penang - Ramli, Muhammad Wafi; Sheikh Dawood, Sharifah Rohayah (GEOGRAFI, 2017)
Homelessness is not a new phenomenon in this country, but in recent years it has become an increasingly prevalent social problem and requires a serious observation of all parties. The homeless issues have also attracted the attention of the public and scholars because its implications are so profound humanitarian issues, especially social exclusion and the issue of sustainability and local communities. The main objectives of this study are to unravel the demographics of the homeless and explore the causes that contribute to their existence, especially in George Town, Penang. This study used quantitative and quantitative methods. The data was collected using questionnaires which were conducted on 30 respondents of homeless, while in-depth interviews were conductedon15 informants of homeless selected from 30 respondents. The data from the questionnaires were analysed using the Statistical Package for Social Science (SPSS) software, while data from the in-depth interviews were analysed by content analysis. The results showed overall homelessness, unemployment, family conflict, the influence of drugs, driven from home and no family members were major contributors to the homeless population in George Town. This study has the potential to contribute the knowledge on the issue of social exclusion which applies to the homeless in Malaysia especially Penang and its implications for the sustainability of community life.